Analysis of Factors Affecting Sharia Stock Investment - Salam, Rangga; Erliyanti; Ridha, Fahrul; Selian, Dian Alasta (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to analyze the factors that influence investors’ decisions in investing in Sharia stocks, including aspects such as Sharia knowledge, risk, return, and other supporting factors. This study uses a qualitative research method based on a literature review. The findings of this study show that investors’ decisions to invest in sharia stocks are influenced by various interrelated factors, including spiritual, economic, and psychological aspects. The main consideration for Muslim investors is adherence to Sharia principles. Investment in the sharia capital market has experienced significant growth in recent years, in line with the increasing public awareness of finance based on Islamic values. The sharia capital market serves as an alternative for investors who want to avoid interest (riba) and financial practices that are not in accordance with sharia principles. According to the Financial Services Authority (OJK), the market capitalization of sharia stocks in Indonesia accounted for more than 60% of the total national stock market capitalization by the end of 2023.